O Papel Moderador da Extroversão no Efeito da Música na Memória Episódica - Pedro Vital Couteiro Silva Delca Guimarães (2022)
Two different experimental paradigms are found in the literature concerning the effects of music on cognitive performance: the background-music paradigm examines music effects during task performance, while the Mozart-effect paradigm presents music before the task. Studies on the effects of background music show mixed results (positive and negative). Listeners' levels of extraversion seem to play a moderating role, in that extraverted individuals benefit from music while introverted ones are harmed by it - something that possibly relates to optimal levels of arousal. However, it is yet unknown whether extraversion moderates the Mozart effect. In order to fill this gap, we examined the effects of sound context (high arousal music, silence, domestic sounds, office sounds) x paradigm (background vs Mozart effect) x extraversion (high vs. low) on episodic memory, meaasuring item memory and source memory in a sample of 40 young adults. We found a main effect of context on item memory, with music eliciting poorer performance than all other contexts. Paradigm and extraversion were irrelevant. For source memory, we found an interaction between context and extraversion, with marginal effects of extraversion for the domestic sounds condition (better performance in high than low extraversion) and music (better in low than high). This may indicate a mechanism of hypermemory for traumatic contexts. Despite its limitations, our findings provide new clues for future research and they point to practical applications in domains such as human resources management or criminal investigation.